Penyusunan Bibliografi Beranotasi Untuk Skripsi Mahasiswa Program Studi Sastra Indonesia Tahun 2009-2013 Koleksi Perpustakaan Jurusan Bahassa dan Sastra Indonesia Universitas Negeri Padang - Mentari, Sri; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article aims to describe the technique of preparation of annotated bibliography thesis students of Indonesian Literature Library collection 2009-2013 Year Indonesian Language and Literature Department, State University of Padang. Making this annotated bibliography can help library user in information retrieval required by pemustaka without having to read the whole essay tersbut. Based on these explanations can be concluded that the stages in the manufacture of annotated bibliography for thesis students of Indonesian Literature Library collection 2009-2013 Year Indonesian Language and Literature Department at the State University of Padang as follows: (1) determination of the title of the bibliography; (2) collecting data yng techniques used in obtaining the data using direct observation to the field; (3) the selection of library materials in the author aims to facilitate the preparation of an annotated bibliography tersbut; (4) grouping aims for the preparation of this biblografi systematically arranged; (5) keyword generation; (6) preparation of the index, which is used to facilitate retrieval pemustaka preformance layout word; (7) Typing bibliography, which consists of writing the author's name, title writing, Legal information (city of publication, publisher, year of publication), and collation; (8) the final editing bibliography which aims to avoid small mistakes which can give rise to doubts about the annotated bibliography. Keywords: bibliography; annotated; collection of the library